Formulasi dan Uji Aktivitas Antiseptik dari Bahan Alam Kulit Jeruk Nipis, Daun Sirih dan Tanaman Bundung terhadap Staphylococcus aureus dan Candida albican - Kurniawati, Darini (FARMASIS: Jurnal Sains Farmasi, 2021)
The use of antiseptics is highly recommended when there is a disease epidemic, even like the current Corona Virus Disease (Covid-19) pandemic, because it can slow the spread of the disease or break the chain of disease spread. The sheath made of lipids is easily damaged by fatty solvents (soap, detergent, alcohol more than 60 percent, chloroform, ether), making the covid-19 virus unable to infect and reproduce. The purpose of this study was to determine the ability to inhibit or kill Staphylococcus aureus and Candida albican bacteria from a combination of betel leaf (Piper betle L) plant extracts, lime peel (Citrus aurantifolia) and bundung plants (Actinuscirpus grossus) from the formulation F20 percent w/v, F30 percent w/v, 40 percent w/v and 50 percent w/v. The research method was experimental by making test formulations with concentrations of F1 20 percent, F2 30 percent, F3 40 percent and F4 50 percent and tested against Staphylococcus aureus and Candida albican bacteria with the disk diffusion method. The results showed that all test formulations had inhibitory power against Staphylococcus aureus and Candida albican and were very strong at 50 percent formulations, while the antiseptic activity in the formulations was 40 percent.